Effect of a dam on epilithic algal communities of a mountain stream: before-after dam construction comparison - Cibils Martina, Luciana (2013)
In this study we evaluated the effect of a dam on epilithic algal communities by analyzing community response after dam construction and by comparing community composition, structure and biomass upstream and downstream of the dam. Samples of epilithic algae and environmental data were collected at each site during high and low water periods before and after dam construction in Achiras Stream (Córdoba, Argentina). Ordinations showed modifications in algal assemblages after dam construction and downstream of the dam. Ordinations also suggested a loss of seasonality at the downstream site since the assemblages were similar between hydrological periods after dam construction. Our results also pointed out that dam construction affected not only the assemblages living at downstream site but also those in the upstream site. Indicator species, obtained by the Indicator Value method, showed that, after dam construction, there could have been an increase in nutrient concentration and a release of plankton from the impoundment. Abundance, richness and diversity were altered after dam construction as assessed by ANOVAs derived from a modified BACI Design. The proportion of earlysuccessional species was higher at the upstream site while late-successional species were dominant at the downstream site, as predicted. Current velocity was higher in the high water period upstream of the dam, with no differences between hydrological periods at the downstream site. So, lower fluctuations in discharge downstream of the dam may have helped succession advance, whereas at the upstream site, mainly during the high water period, floods appear to have caused sloughing of life forms from the outer layers of the biofilm, resetting the algal community to early successional stages. It may be concluded that the dam affected algal community and favored succession advance mainly by reducing current velocity and flow fluctuations.